Impact of Caring for Children with Congenital Heart Disease on Nurses’ Lives: A Qualitative Study - Ayşe Ay; İlçim Ercan Koyuncu; Aylin Günay (Mediterranean Nursing and Midwifery)
Objective: Advances in technology have improved survival rates for children with congenital heart disease (CHD), leading to additional surgery and longer hospital stays. Nurses are essential healthcare professionals involved in these challenging processes. This study aimed to explore the impact of caring for children with CHD on the lives of nurses. Method: A qualitative-descriptive research design was employed. The study was conducted with 15 nurses caring for children with CHD at a foundation university hospital in Turkey. Data were collected using a “demographic information form” and a “semi-structured interviews” through face-to-face interviews. Nurses were asked to discuss the positive and negative effects of caring for children with CHD on their own lives. The interviews were recorded and professionally transcribed. Two researchers thematically analyzed the transcripts using MAXQDA. The study was conducted using the consolidated criteria for reporting qualitative research criteria. Results: The average age of the nurses was 30.53±5.14 years, and 73.33% had more than 5 years of experience caring for children with CHD. The results of the individual interviews revealed five main themes and 14 subthemes. These main themes are (i) Strengthening knowledge and skills, (ii) Interaction with the child, (iii) Psychosocial empowerment, (iv) Emergence of negative impacts, and (v) Overcoming challenges in professional life. Conclusion: Caring for children with CHD positively and negatively impacts nurses’ lives. To mitigate the negative effects on nurses, providing physical and psychological support and empowerment are crucial.